(untitled) (Journal of Engineering, 2018)
Porcelain is one of the most important ceramic materials with a wide range of traditional and technical applications. Since most mixtures of porcelain have a high sintering temperature, bentonite has been added in this research to improve the characteristics of sintering and burning. The porcelain mixture consisted of the following Iraqi raw materials: 30% wt kaolin, 30 wt% non-plastic clay (grog), 10% wt sodium feldspar, 10 wt% potassium feldspar and 20 wt% flint. After the mechanical mixing process and transfer the powder mixture to the slurry by adding distilled water, then different weight percentage of the sodium bentonite(0, 2.5, 5, 7.5 and 10) wt% was added. The specimens were prepared by using the solid casting method, and after the drying process, the specimens were burned at1100 oC. The results of x-ray diffraction showed that bentonite reduced the crystallization of the main ceramic phases (mullite, quartz), which stimulates the appearance of amorphous glass phases. Also, the loss of mass on ignition increased when the addition of bentonite from 5.66% to 8.2%. There was also a great convergence between the granules of porcelain when adding bentonite and thus increase the shrinkage of the dimensions from 9.33% to 12.37 %. This led to increasing the bulk density from 1.97 g/cm3 to 2.67 g/cm3 at firing temperature 1100oC, and the porosity was decreased from 17.1% to 1.44%. Diametrical strength and flexural strength (bending) increased with bentonite (14.88 to 34.46MPa), (6.2 to 8.65 MPa), respectively.